Federalism and the politics of fiscal responsibility laws: Argentina and Brazil in comparative perspective. (3rd May 2016) - Gordin, Jorge P.
ABSTRACT: This article advances an institutionalist perspective to address a subset of issues that led to the relative success of Brazil and the absolute failure of Argentina in confronting the financial crisis of the late 1990s. It adds to the literature on the politics of fiscal federalism, documenting that fiscal crises prompt policy responses whose effects are mediated by institutional choice and the broader political dynamics and the incentives both generate. By analysing the adoption of fiscal responsibility laws in two federal polities that had been challenged by similar financial and territorially induced constraints, it tentatively shows that success in containing subnational fiscal profligacy, which has been causally related to the national overall financial weakness to confront the late 1990s crises, is contingent upon the internalisation of the value of fiscal responsibility by subnational administrations. These findings suggest that prevailing views on subnational actors as debt-ridden and passive spectators of fiscal policies for which national governments had taken full responsibility should be reconsidered. Given favourable institutional incentives, subnational interests are not necessarily incompatible with national programmes of fiscal adjustment and stability.